The contribution of statistical learning to language and literacy acquisition - Wu, Denise Hsien; Bulut, Talat (Academic Press Inc., 2020)
Acquisition and processing of written and spoken language is an impressive cognitive accomplishment considering the complexity of the tasks. While only humans seem to have evolved to the fullest extent the capacity that underpins these remarkable feats of development and civilization, the exact nature of such capacity has been subject to ongoing research. In this chapter, we focus on language competence and what makes it unique among the communication systems of different species. We then elaborate on the classical debate between nativist and environmentalist accounts of language acquisition, with reference to evidence for and against the critical period hypothesis. After introducing the regularity embedded in different languages and particularly in drastically different orthographies, we present behavioral and neurophysiological evidence for the sensitivity to systematic mapping between orthography and phonology. Because learning to read is to master such mapping, we assume that the ability to use statistical learning to appreciate the dependency among items would contribute to literacy acquisition. Empirical results from behavioral and neuroimaging experiments conducted in our and other laboratories provide support for the close link between statistical learning and literacy acquisition in native and foreign language. Such findings highlight the significance of domain-general statistical learning to domain-specific language acquisition, and point to an important direction for theories and practices of language education.
Keywords: Consistency Effect; Logographic Orthography; Reading; Second Language Acquisition